Thermal efficiency experimental evaluation of solar flat plate collectors when introducing convective barriers - Garcia, Rafael Paiva; Oliveira, Santiago del Rio [UNESP]; Scalon, Vicente Luiz [UNESP] (Elsevier, 2019)
The increase of renewable sources in power generation is a global concern. Research and development of renewable energy devices use are leading to changes in the global energy mix. In this scenario, solar energy has a great potential for new applications. Thus, this study analyzes possible improvements in the thermal efficiency of solar flat plate collectors commonly used in domestic water heating systems. The influence of the inclusion of convective barriers inside the air cavity located between the absorber plate and the glass cover is evaluated based on the increase of the thermal efficiency in the solar collector. The use of these barriers limits the space between the absorber plate and the glass cover, which may reduce heat losses in some conditions. The experimental analysis was performed using four solar collectors with one to four convective barriers. The results obtained were compared with a reference solar collector, without any barrier. An instrumented test bench was built to measure the flat plate solar collector thermal efficiency. The results showed that there was no significant variation in solar radiation absorption since the maximum thermal efficiency remains unchanged. However, the barriers inclusion implies in changes in heat loss. The experimental data shown that changes in heat loss are −2,2%, −5,3% and 2,9% for two, three and four barriers, respectively. In this way, the convection barriers are able to reduce the heat loss in two cases, but increase the heat loss in one case. This result indicates that there is an optimal number of convective barriers for each solar collector design.
Keywords: Free convection in cavities; Solar energy thermal efficiency; Solar flat plate collector; Transparent insulation